2022
DOI: 10.3389/fimmu.2022.874108
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Disease Control in First-Line Therapy-Resistant Mucous Membrane Pemphigoid and Bullous Pemphigoid with Omalizumab as Add-On Therapy: A Case Series Of 13 Patients

Abstract: The role of IgE autoantibodies has been demonstrated in the pathogenesis of bullous pemphigoid for many years. Recently, omalizumab (OMZ), a humanized monoclonal anti-IgE antibody that depletes total serum IgE, has been used off-label in a few case series of bullous pemphigoids demonstrating a rapid efficacy and allowing significant improvements or complete remission as add-on therapy in first-line treatment-resistant patients. Herein, we report the largest retrospective study to evaluate OMZ effectiveness in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Other studies reported variable data on the value of specific IgE in BP, differing from 22% to 100% [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. This variation could also be attributable to the lack of standardization in methods used for detection with different sensitivities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies reported variable data on the value of specific IgE in BP, differing from 22% to 100% [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. This variation could also be attributable to the lack of standardization in methods used for detection with different sensitivities.…”
Section: Resultsmentioning
confidence: 99%
“…Another case series reports high levels of liver enzymes and thrombocytopenia. Two patients developed a mild flu-like illness after injection, which was easily managed with paracetamol and disappeared from the sixth injection onwards [ 50 , 78 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“…Instead of dapsone, classical immunosuppressants as mycophenolate or azathioprin can be employed, while rituximab is considered an off-label ultima ratio, especially in severely scarring courses ( 19 21 ). Finally, other approaches with intravenous immunoglobulins or omalizumab have been reported to be useful as well ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…IgE-mediated autoimmunity may be involved in BP blister development ( 28 , 29 ). IgE autoantibodies target the intracellular domain of BP180.…”
Section: Immune Cellsmentioning
confidence: 99%